2014
DOI: 10.1055/s-0034-1379008
|View full text |Cite
|
Sign up to set email alerts
|

ortho-Ketimines of 1,8-Bis(dimethylamino)naphthalene: Synthesis, Hydrolytic Stability and Transfer of Basicity from Proton Sponge Moiety to the Imino Function

Abstract: A series of 2-ketimines and 2,7-diketimines of 1,8-bis(dimethylamino)naphthalene (proton sponge, DMAN) have been obtained and converted into the corresponding ketones via acidic hydrolysis. Investigation of structural and spectral properties of DMAN-based imines led to the conclusion that their unusual hydrolytic stability results from a combination of different factors the most important of which is a strong electron-donor effect of peri-dimethylamino groups.Imines are of common interest in organic synthesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In other words, in the case of 7b’ , steric pressure of the trimethoxyphenyl substituent facilitates the 1-NMe 2 group’s out -inversion which is stabilised by an IHB, forming N(sp 3 )/N(sp 2 ) type of proton sponges, which were recently reported in our paper [18]. It was previously shown that the in,out -conformation can be stabilised by placing the following functionalities in position 2(7): tertiary alcoholic groups which are able to form the O–H···N IHB [1617 19], bulky substituents rendering a steric pressure onto the 1-NMe 2 group [7,20], or a metal atom coordinating the NMe 2 group as a ligand causing its inversion [21] (Scheme 9). A possibility of out -protonation of 1,8-bis(dimethylamino)naphthalene was discussed in our recent paper [15], while it is experimentally demonstrated here for the first time.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…In other words, in the case of 7b’ , steric pressure of the trimethoxyphenyl substituent facilitates the 1-NMe 2 group’s out -inversion which is stabilised by an IHB, forming N(sp 3 )/N(sp 2 ) type of proton sponges, which were recently reported in our paper [18]. It was previously shown that the in,out -conformation can be stabilised by placing the following functionalities in position 2(7): tertiary alcoholic groups which are able to form the O–H···N IHB [1617 19], bulky substituents rendering a steric pressure onto the 1-NMe 2 group [7,20], or a metal atom coordinating the NMe 2 group as a ligand causing its inversion [21] (Scheme 9). A possibility of out -protonation of 1,8-bis(dimethylamino)naphthalene was discussed in our recent paper [15], while it is experimentally demonstrated here for the first time.…”
Section: Resultssupporting
confidence: 53%
“…Indeed, the X-ray analysis shows that compound 6a in the solid state exists in the E -form stabilised by the N−H···O intramolecular hydrogen bond (IHB) with an ortho -OMe group (Fig. 2), while compound 4a , as it was revealed in our previous work [7], exists exclusively as a Z -isomer (Fig. 2).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Organometallics play a key role in the preparation of naphthalene proton sponges, which are widely known for their outstanding basicity (pKa (1) = 12.1 in H2O [5], 18.62 in MeCN [6], 7.5 in DMSO [7]). Dozens of ortho-, para-and even meta-derivatives of 1 were obtained from organolithiums 2-6 (Scheme 1) [8][9][10], which not only made it possible to establish the relation between structure and basicity of these interesting compounds [11,12], but also revealed their unusual reactivity leading to the formation of key heterocyclic systems, such as indoles [10,13], pyrazoles [14], isoxazoles [14], quinolines [15], quinasolines [16]. Moreover, in the past two decades, naphthalene proton sponges drew additional attention as a convenient core for the development of superbasic heterogeneous catalysts [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%